Vaccination Coverage and Associated Factors among Children Aged 12–23 Months in Debre Markos Town, Amhara Regional State, Ethiopia - Tenaw Gualu; Abebe Dilie (Advances in Public Health)
Introduction. Vaccination is the administration of a vaccine or a biological substance intended to stimulate a recipient’s immune system to produce antibodies or undergo other changes that provide future protection against specific infectious diseases. Objective. To determine vaccination coverage and associated factors among children aged 12–23 months in Debre Markos town 2016. Methods. Community-based cross-sectional study was employed among 288 mothers/caretakers to child (12–23 months) pair. Study populations were selected using systematic random sampling technique. Structured interviewer administered questionnaires were used to collect data. Variables with P value of less than 0.05 in multivariate analysis were considered as statistically significant at 95% CI. Result. About 264 (91.7%) of children were completely vaccinated. Male birth 3.24 (1.16–9.04), wanted pregnancy 2.89 (1.17–7.17), having at least two ANC follow-ups 4.04 (1.35–12.06), and short distance from vaccination site 3.38 (1.29–8.86) were found positively associated with complete immunization. Conclusion and Recommendation. There was relatively high immunization coverage in the study. Child’s sex, ANC follow-up, type of pregnancy, and distance from health institution were factors associated with complete vaccination. Preventing unwanted pregnancy and promoting ANC and postnatal follow-up should be strengthened. Vaccination sites should also be further expanded.